2005
DOI: 10.1093/neurosurgery/57.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Heterotopic Ossification in Cervical Disc Replacement: A Prospective Multicenter Clinical Trial

Abstract: There is a strong association of the occurrence of HO with subsequent loss of movement of the implanted cervical artificial disc. We have found that sex and age are two possible risk factors in the development of HO after cervical disc replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 11 publications
4
87
1
5
Order By: Relevance
“…7,28,39,40,42,50 Chen et al 12 report a pooled prevalence of HO of 44.6% (17.8 to 72.3%) and of advanced HO (Grade III and IV) of 11.1% (4.2 to 23.1%) after 1 year and of 58.2% (28.8% to 78.5%) and 16.7% (8.5 to 32.3%) 2 years after cTDR, respectively. Current publications tend to report higher incidences of HO with 17.8% HO 1 year after implantation of the Bryan disc (including 6.7% Grade III or IV), 34 7.9% Grade IV 2 years after Mobi-C implantation, 5 or an overall HO occurrence of 94.1%. 41 Yi et al 57 observed an overall HO rate for 3 different cTDRs of 40.6% and Brenke et al 10 found HO (Grade III and IV) in 17.4% after 18 months using fluoroscopy and even higher incidences using CT-based analysis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…7,28,39,40,42,50 Chen et al 12 report a pooled prevalence of HO of 44.6% (17.8 to 72.3%) and of advanced HO (Grade III and IV) of 11.1% (4.2 to 23.1%) after 1 year and of 58.2% (28.8% to 78.5%) and 16.7% (8.5 to 32.3%) 2 years after cTDR, respectively. Current publications tend to report higher incidences of HO with 17.8% HO 1 year after implantation of the Bryan disc (including 6.7% Grade III or IV), 34 7.9% Grade IV 2 years after Mobi-C implantation, 5 or an overall HO occurrence of 94.1%. 41 Yi et al 57 observed an overall HO rate for 3 different cTDRs of 40.6% and Brenke et al 10 found HO (Grade III and IV) in 17.4% after 18 months using fluoroscopy and even higher incidences using CT-based analysis.…”
Section: Discussionmentioning
confidence: 94%
“…9,25,36,40,54 However, there remains critical debate on cTDR mainly regarding indication, costs, and heterotopic ossification (HO). 4,10,12,34,38,41,50,52,57,58 HO may not affect clinical outcome 5,33,38,52,57 or be less relevant in the absence of clinical symptoms, 6,28 but advanced HO potentially compromises segmental mobility with an unknown impact on sagittal profile, long-term clinical results, and ASD.…”
mentioning
confidence: 99%
“…Finally, 38 studies were included in the meta-analysis. [3,812,1647] Figure 1 exhibits the details of screening process.…”
Section: Resultsmentioning
confidence: 99%
“…However, the correlation was almost marginal ( p =0.091), suggesting possible significance in a long-term follow-up. Many studies have examined risk factors for HO after cervical TDR, such as male sex, old age, longer post-operative period, prosthesis type, and preoperative calcification of longitudinal ligaments and osteophyte5,15,20,34). The reason for the high incidence of HO in our study was thought to be the difference in sex ratio (male : female=12 : 5) and prosthesis type.…”
Section: Discussionmentioning
confidence: 73%